Mount S. Benedict, Trinidad, B.W.I. : Future Monastery - (:unkn) unknown (My University, 2010)
Photo of Mount St. Benedict in Trinidad and Tobago. No. 12.
Colour: White, Grey and Cream Hues; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Catholic Church--Trinidad and Tobago; Monasteries--Trinidad and Tobago; Christianity--Trinidad and Tobago; Catholics--Trinidad and Tobago; Mt. St. Benedict; Church architecture--Trinidad and Tobago; Religious communities--Trinidad and Tobago; Church buildings--Trinidad and Tobago